Impact of social concern on cyberbullying perpetration in Iran: direct, indirect, mediating, and conditioning effects in Agnew’s social concern theory - Shadmanfaat, Seyyedeh Masoomeh (Shamila) (Deviant behavior, 2021)
Social concern theory is an integrative theory that considers human nature in multiple dimensions. This study tested an aspect of social concern theory using self-reported data on cyberbullying. We collected original data from a sample of Iranian high school students and examined direct, indirect, mediating, and conditioning effects of social concern on the perpetration of cyberbullying. It was shown that the inclination to social concern has direct, indirect, mediating, and conditioning effects on cyberbullying perpetration. Furthermore, we found significant relationships between the four elements of social concern and moral intuitions contributing to sympathy and empathy, and we found that the desire for close ties to others contributes to the inclination to conform. These results provided strong support for social concern theory.